The Qur'an's Surah Al-Imran 159 And Surah Al-Hujurat 11–12 Depict Moral Education - Alimudin, Alimudin; Muhajir, Muhajir; Rahmi , Novita (Al-Insyiroh: Jurnal Studi Keislaman, 2023)
This article aims to find out how the concept of moral education is in the Qur'an Surah Al-Imran verse 159 and Surah Al-hujurat verses 11-12. This research is backgrounded by the emergence of the phenomenon of moral decline that occurs among young people. One of the causes of moral deterioration is the presence of criminal activity and fights. The Qur'an is very important for mankind, especially for Muslims. Therefore, we are obliged to understand its content and content. The purpose of this study is to find out how the concept of moral education in the Qur'an surah Al-Imran verse 159 and surah Al-hujurat verses 11-12. This research is a library research using an interpretation approach. The author seeks to understand the concept of moral education by using interpretation as a supporting analytical tool, such as the books of interpretation and also the interpretations of educational figures related to moral education. Therefore, there are two main sources that are used as the basis for this study, namely primary and secondary data sources. The primary data sources here are obtained from the Qur'an, while the secondary data sources obtained use references in the form of books, articles, magazines, and so on, as well as from educational figures, whose materials are related to moral education and several topics that support this research. The results of this study show that the values of moral education contained in surah Al-Imran verse 159 and surah Al-Hujurat verses 11-12 are that humans are encouraged to always be gentle towards their relatives, sincere when giving forgiveness to others, respect the opinions or suggestions of others, abstain from attitudes and deeds of making fun of others, and abstain from prejudiced attitudes and deeds towards others, Because muslims are actually brothers.